Why and how to spare the hippocampus during brain radiotherapy: the developing role of hippocampal avoidance in cranial radiotherapy - Kazda, Tomas; Jancalek, Radim; Pospisil, Petr; Sevela, Ondrej; Prochazka, Tomas; Vrzal, Miroslav; Burkon, Petr; Slavik, Marek; Hynkova, Ludmila; Slampa, Pavel; Laack, Nadia N (Radiation oncology (London, England), 2014)
The goal of this review is to summarize the rationale for and feasibility of hippocampal sparing techniques during brain irradiation. Radiotherapy is the most effective non-surgical treatment of brain tumors and with the improvement in overall survival for these patients over the last few decades, there is an effort to minimize potential adverse effects leading to possible worsening in quality of life, especially worsening of neurocognitive function. The hippocampus and associated limbic system have long been known to be important in memory formation and pre-clinical models show loss of hippocampal stem cells with radiation as well as changes in architecture and function of mature neurons. Cognitive outcomes in clinical studies are beginning to provide evidence of cognitive effects associated with hippocampal dose and the cognitive benefits of hippocampal sparing. Numerous feasibility planning studies support the feasibility of using modern radiotherapy systems for hippocampal sparing during brain irradiation. Although results of the ongoing phase II and phase III studies are needed to confirm the benefit of hippocampal sparing brain radiotherapy on neurocognitive function, it is now technically and dosimetrically feasible to create hippocampal sparing treatment plans with appropriate irradiation of target volumes. The purpose of this review is to provide a brief overview of studies that provide a rationale for hippocampal avoidance and provide summary of published feasibility studies in order to help clinicians prepare for clinical usage of these complex and challenging techniques.
Keywords: prognóza; celková dávka radioterapie; Radiotherapy Dosage; léčba šetřící orgány; Prognosis; nádory mozku; Brain Neoplasms; Hippocampus; plánování radioterapie pomocí počítače; lidé; Cranial Irradiation; Organ Sparing Treatments; Humans; hipokampus; kraniální ozáření; Radiotherapy Planning, Computer-Assisted